2002
DOI: 10.1002/ajpa.10038
|View full text |Cite
|
Sign up to set email alerts
|

Discerning evolutionary processes in patterns of tamarin (genusSaguinus) craniofacial variation

Abstract: Quantitative genetic theory specifies evolutionary expectations for morphological diversification by genetic drift in a monophyletic clade. If genetic drift is responsible for the evolutionary morphological diversification of a clade, patterns of within- and between-taxon morphological variance/covariance should be proportional. We tested for proportionality of within- and between-species craniofacial morphological variation in 12 species of tamarins (genus Saguinus). We found that within- and between-taxon mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
199
2
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(206 citation statements)
references
References 32 publications
3
199
2
2
Order By: Relevance
“…Each analyzed hierarchical level contains at least three populations. Because of the inherently small sample sizes, individual fossil specimens are taken to represent population means; whether these populations represent different species or are time-successive taxa should not affect the analysis, as this approach has been shown to work at different levels in a phylogeny (13,17,18). As the fossil record does not allow for a direct estimate of fossil intraspecific variation, extant variation in humans and our two closest living relatives (chimps and gorillas) is substituted for withinpopulation variation of fossil species (see below).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each analyzed hierarchical level contains at least three populations. Because of the inherently small sample sizes, individual fossil specimens are taken to represent population means; whether these populations represent different species or are time-successive taxa should not affect the analysis, as this approach has been shown to work at different levels in a phylogeny (13,17,18). As the fossil record does not allow for a direct estimate of fossil intraspecific variation, extant variation in humans and our two closest living relatives (chimps and gorillas) is substituted for withinpopulation variation of fossil species (see below).…”
Section: Methodsmentioning
confidence: 99%
“…However, the assumption of constancy in covariation patterning is problematic. Although a number of studies have shown that there are many common aspects to morphological variation and integration in the primate cranium, and especially in the face (13,(22)(23)(24)(25)(26)(27), it is also true that there are differences. To conservatively account for the possible effects of small differences in covariance (CV) structure (22, 28), we use three extant models rather than just one, as we realize that patterns of variation are not homogenous (although they are similar; see ref.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that they should be classified as separate species rather than subspecies, based on their finding that "morphological distances among marmosets are s m lar to or h gher than d stances found among other related taxa usually accepted as good species, like the tamarins (Moore and Cheverud 992; Ackermann andCheverud 2000, 2002)" (p.17). They also failed to find evidence for intergradat on along contact zones, but nstead "a sharp, steep morphological boundary between taxa with no trend of species being more morpholog cally s m lar at contact zones than at other parts of the r ranges.…”
Section: "Jacchus" Group Marmosets -Species or Subspecies?mentioning
confidence: 99%